Letter (copy) : re shipment of surgical dressings to Spain - Morgan, H. B. (Hyacinth Bernard Wenceslaus Morgan), 1885-1956
041-0091-001 JB/DM. HBM/EKK/128. Social Insurance. 24th November, 1936. Messrs. J.A. Billmeir & Co., Holland House, Bury Street, LONDON. E.C.3. Dear Sir, re Shipment of Surgical Dressings to Spain. I beg to thank you for your letter of the 18th November, and am obliged for the invoice of the charges. I note, however, that the gratuity given to the Captain amounts to the sum of £5., and I hope you will not mind if I say that I think this rather heavy, as in my telephonic communication with you I mentioned the sum of £2,, or at the most £3. I appreciate, of course, that the Captain had to take care of the cargo, and I am very grateful, but I think the honorarium, having regard to the goods, rather heavy. I shall be glad to hear from you on this matter before I pass on the invoice for settlement. Yours faithfully, Medical Adviser. 292/946/41/91